2018
DOI: 10.1186/s13568-018-0577-4
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of a novel α-1,3-arabinofuranosidase from Penicillium oxalicum sp. 68

Abstract: The discovery and creation of biocatalysts for plant biomass conversion are essential for industrial demand and scientific research of the plant cell wall. α-1,2 and α-1,3-l-arabinofuranosidases are debranching enzymes that catalyzing hydrolytic release of α-l-arabinofuranosyl residues in plant cell wall. Gene database analyses shows that GH62 family only contains specific α-l-arabinofuranosidases that play an important role in the degradation and structure of the plant cell wall. At present, there are only 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
(46 reference statements)
0
7
0
2
Order By: Relevance
“…3). Activity on pectin-related arabinan has also been reported for related enzymes, such as Abf62A from Penicillium oxalicum [33] and Abf62A and Abf62C from Mycothermus thermophilus [34]. It has been suggested that this activity is particularly related to the a-1,3-L-arabinose decorations of the a-1,5-L-arabinose backbone or arabinan [32].…”
Section: P Subrubescens Abfs Display Highly Diverse Activities On Nat...mentioning
confidence: 81%
“…3). Activity on pectin-related arabinan has also been reported for related enzymes, such as Abf62A from Penicillium oxalicum [33] and Abf62A and Abf62C from Mycothermus thermophilus [34]. It has been suggested that this activity is particularly related to the a-1,3-L-arabinose decorations of the a-1,5-L-arabinose backbone or arabinan [32].…”
Section: P Subrubescens Abfs Display Highly Diverse Activities On Nat...mentioning
confidence: 81%
“…39 P. oxalicum is applied in the industrial production of glycoside hydrolase. 40 A study suggests that this species has potential applications in βxylosidase production. 41 E. amstelodami (57.1% frequency of occurrence), which is widely found in Fuzhuan brick tea and Pu'er tea, is believed to be one of the spices that form the "golden flower" in dark tea.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Strain P. oxalicum sp. 68 was isolated from soil in Changbai Mountain (Jilin Province, China), and stored in China General Microbiological Culture Collection Center (collection number CGMCC 7.328) [ 27 ]. P. pastoris GS115 and p PICZα A (Novagen, USA) were used as host and expression vectors, respectively.…”
Section: Methodsmentioning
confidence: 99%